Analysis of Agile Governance Implementation in Building Integrity Zone at UPTD Health Training of West Java Province. - Kusmana, Odang; Sarihati, Tati; Rohayati, Yeti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze the implementation of Agile Governance in building Integrity Zone at UPTD Health Training of West Java Province. The research approach used is qualitative with a case study method, and data collection techniques include field observations, interviews, documentation, and in-depth document analysis. The theoretical foundation of this research refers to the concept of Agile Governance from Luna et al. (2015), which includes six main principles: Good Enough Governance, Business-driven, Human-focused, Systematic and Adaptive Approach, and Simple Design and Continuous Refinement. These principles are used to evaluate the extent to which organizational flexibility and responsiveness can be applied in bureaucratic reform and service quality improvement. The results show that the implementation of Agile Governance at UPTD Health Training has been quite optimal, especially in terms of technology integration, human resource capacity building, and internal policy simplification. However, there are still some challenges such as digitalization expansion, increased employee engagement, and more flexible procedure adjustments.